The Influence of Good Corporate Governance, The Role of Internal Audit, The Effectiveness of Internal Controls and The Appropriate of Compensation on Fraud Trends - Irwansyah Irwansyah; Wilensi Zega (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2023)
Fraud is an act that was carried out intentionally for personal or group purposes, where the intentional action has caused harm to certain parties or certain agencies. This study aims to determine the effect of corporate governance, the role of internal audit, the effectiveness of internal controls and the suitability of compensation to the tendency of fraud. The type of data used is quantitative data. The resources used are primary data. The population in this study are business managers, sales managers, finance managers and HR managers. The sampling technique used was purposive sampling method with 10 companies consisting of 49 respondents. The data in this study were processed using multiple linear regression with the help of the SPSS version 25 application. The results of this study indicate that (1) corporate governance has an effect on the tendency of fraud (2) the role of internal audit has a negative effect on the tendency of fraud, (3) the effectiveness of internal control has a negative effect on the tendency of fraud in BUMN in Bengkulu City, (4) the suitability of compensation has an effect on negative to the tendency of fraud.